PENGEMBANGAN KEHIDUPAN BERAGAMA MAHASANTRI MELALUI PROGRAM MA'HAD AL-JAMIAH IAIN CURUP - Putri Rachmawati Wahyuni Asyri Ep; Rifanto Bin Ridwan; Emmi Kholilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The religious life of students is a crucial aspect that needs to be developed in Islamic higher education to shape a generation that not only excels academically but also possesses a sound understanding and practice of Islamic values. One form of development is the Ma'had Al-Jamiah Program, which integrates academic education with dormitory-based religious guidance. This study aims to analyze the development of the religious life of students through the Ma'had Al-Jamiah Program at IAIN Curup. The study used a qualitative method with a phenomenological approach. Data were obtained through in-depth interviews and documentation of students participating in the development program. The results indicate that the Ma'had Al-Jamiah Program contributes to improving religious discipline, strengthening religious understanding through memorization and muhadharah activities, and shaping morals and social behavior in accordance with Islamic values. Dormitory life also encourages the development of discipline, responsibility, caring, and the habit of maintaining harmonious relationships with others. Thus, the Ma'had Al-Jamiah Program plays a role in developing the religious life of students by strengthening worship, religious understanding, and habituating Islamic values ​​in daily life.